Teenagers’ Opinions on Parental Involvement in Compulsory Schools in Iceland - Jónsdóttir, Kristín (International Journal about Parents in Education, 2023)
Students’ voices in research on parental involvement in schools are rather weak since many studies report only on opinions of parents and school personnel. This paper draws on findings from a study in 14 compulsory schools and uses data from questionnaires from students in 7th to 10th grade (n=1821). The issue, students’ wishes for parents’ participation, is approached from a systemic perspective; Bronfenbrenner´s ecological systems theory, Epstein´s model of family-school-community partnership, and Pasi Sahlberg´s Nordic point of view are applied. Multiple regression analysis testing revealed that gender, grade, and student confidence in his or her learning ability explained 9.4% of the variance (R2) in students’ wishes. School experiences were added in a second model and explained an additional 8.8% of the variance (R2 change). Believing that parents’ support is important for achievement and believing that discipline and peaceful class environment affects achievement were the two variables added in the third model of the regression analysis, and the overall explanation of the model was raised to 27.6% (R2). Implications are that home-school cooperation on a lower-secondary level should focus more on activities related to the academic side of school life. Also, schools should take action in bettering the quality of factors related to students’ school experience since that could result in an increase in students’ interest for parental participation, which in turn contributes positively to academic achievement.